Reliability and validity of the soccer specific INTER field test - Aandstad, A.; Simon, E. V. (Journal of Sports Sciences, 2013)
The aims of this study were to explain how the Intermittent Endurance Running (INTER) test is executed, describe physiological responses during testing, and evaluate reliability and content validity in this new soccer specific test. The test consists of 20 m shuttle running, interspersed with straight sprints, agility sprints, walking and resting. Shuttle run speed is increased at each level until exhaustion. Thirteen male professional players participated in the present study. Exercise tolerance time, distance covered, mean blood lactate and mean heart rate were 25:51 ± 2:41 min, 2892 ± 324 m, 5.5 ± 1.2 mmol/L and 161 ± 11 beats/min, respectively, during the INTER test. Sprint and agility performance decreased significantly at higher levels. Eight of the players performed a retest for reliability evaluations. Mean difference ± 95% limits of agreement, coefficient of variation (CV) and intraclass correlation coefficient (ICC) for exercise tolerance time between test and retest were -00:41 ± 02:25 min, 2.5% and 0.75, respectively. The CV for sprint and agility performance between test and retest was <1%. The INTER test mimics soccer games on distance/time ratio, frequency of sprints, heart rate and blood lactate values, and could be an alternative field test for evaluating essential physical performance aspects in soccer players.